Dietary and environmental factors associated with symptoms or diagnosis of asthma in Cape Town school children : findings from the International Study of Asthma and Allergies in Childhood (ISAAC) phase three study - Mahlati, Unati (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 103-109).